Produção de nanofibras pelas técnicas de Solution Blow Spinning (SBS) e Supersonic Solution Blowing (SSB) e suas aplicações para conversão e armazenamento de energia - Silva, Vinícius Dias (2023)
A rapid energy transition to less polluting sources, as the global urgency demands, will not be driven by a single technology. It is necessary that all available technologies evolve to meet the needs of each demand of the energy ecosystem, that is, the conversion, storage, and distribution of energy. Thus, it is imperative that intermittent means of energy conversion, such as wind and solar, are working in an integrated manner with advanced storage network systems, such as supercapacitors and batteries. In the other line of action, green hydrogen (H2) has been considered as one of the most promising sources of renewable fuel to meet the growing global demand. Among the green H2 production methods, the route through water electrolysis can produce high purity H2 in a completely sustainable way. In this thesis, we developed a study using two techniques the solution blow spinning (SBS) and supersonic solution blowing (SSB) in the production of nanofibers to be applied as electrode materials in heterogeneous catalysis and as electrodes in electrochemical energy storage devices (supercapacitors, battery-type electrodes, lithium-ion anodes). Focusing on the possible large-scale application, the reasons, and moments in which the techniques should be applied were discussed. As well as nanofibers were synthesized based on abundant materials and with good electrochemical properties, such as carbon and transition metals, which may replace the noble metals that make current technologies more expensive. As a result, an unprecedented study was successfully introduced to obtain hollow nanofibers, and when applied to the production of oxide nanofibers based on Ni/Ce, it made it possible to obtain battery-type electrodes with a capacity superior to that of other reported works. And high entropy oxide nanofibers produced for the first time by the SBS technique, were used directly as electrocatalysts, revealing global catalytic performance (activity and stability) applicable. Here, it was demonstrated that using carbon nanofibers as a support for nanoparticles to act as active catalytic centers is a highly rational strategy for the development of durable self-supporting electrodes, as it prevents deactivation and degradation by coalescence. Carbon nanofibers (micro and mesoporous) with ultra-high surface area above 4000 m2/g were also obtained, revealing high performance as electrical double layer supercapacitors. And, for the first time in the literature, a fundamental area-diameter coefficient of the fibrillar electrode [FEADC, in m2/(g nm)] was proposed, which unifies the parameters diameter of the nanofibers and surface area, where it was argued and suggested that this coefficient is implemented in the analysis of nanofibrous supercapacitors electrodes. When these same ultra-high surface area nanofibers were applied as an anode for lithium-ion batteries, they showed capacity values superior to the theoretical graphite, which is the electrode material used in commercial lithium-ion batteries. In short, the application of SBS and SSB techniques have been successfully explored in the design of self-supporting nanofibrous electrodes for electrochemical energy conversion and storage devices.